Aspetti nutrizionali dei pasti di una mensa per i poveri: l’esperienza dell’Opera di San Francesco di Milano, Italy - Maioli, Claudio; Colosio, Claudio; Muzio, Fulvio; Cioni, Federico (Progress in Nutrition, 2016)
Objectives: We report the experience of San Francesco Opera soup kitchen in Milan. We analyzed: 1) user nationality; 2) nutritional composition of 869,516 meals served in 2014 (average 2,800 meals per day), with the aim of highlighting any nutritional deficiencies. Setting: Milan, Italy. Design: We report a quantitative analysis of macro and micronutrients of all the meals dished (database: Souci “Comparative Tables of Food”), comparing them with the reference values for the Italian population (LARN 2012). Sample: About 2,800 meals a day for 6 days a week from Monday to Saturday served in a year (2014). Menus are of two types: winter menu (7 months, from 01/01 to 04/30 and from 01/10 to 31/12) and summer menu (5 months, from 1/5 to 30/09). Results: 2039 Kcal have been dished out from winter menu (15% protein, 29% fat, 56% carbohydrate) vs 2146 kcal from summer menu (15% protein, 28% fat, 57% carbohydrate). Conclusions: Macronutrients and micronutrients are well represented both in summer and in winter menu. We report a lack of calcium, vitamin D and zinc due to the scarcity of foods such as milk and dairy products that must be integrated. Salt appears to be higher than recommended.